Dual-band frequency reconfigurable 5G microstrip antenna - Yusnita Rahayu; Yoga Bayu Pradana; Yoshihide Yamada (Universitas Mercu Buana, 2023)
Microstrip Antenna is widely developed and used in modern telecommunications equipment because of its advantages. Microstrip antenna is also used in 5G development which is expected to increase communication capacity and also be able to provide very large data rates. The frequency used in 5G is 28, 38, and 78 GHz. However, the 5G network with high frequency has a weakness: transmitted waves are vulnerable to weather because of their dense waveform. Therefore, the multiband is used to support different frequencies in one antenna. Furthermore, antenna reconfiguration is used to set the antenna to work on a different frequency and adjust different radiation patterns depending on the needs without changing the form of the antenna. This paper proposes the dual-band frequency reconfigurable antenna with RT Duroid 5880 as its substrate using PIN diodes placed between the main patch and secondary patch element and simulated on CST software for 28 GHz and 38 GHz with two conditions, ON and OFF. Both simulated and measured results show that the antenna can work well as intended. During the OFF condition, the antenna only works at 38 GHz, while in the ON condition, the antenna works at 28 GHz and 38 GHz, respectively.